The influence of employees’ parents on work-family balance in Taiwan: implications for organisational behaviour and wellbeing - Wu, Chih-Ying (2015)
Work-family research in Chinese societies often directly adopts the Western work-family model and rarely attempts to consider cultural differences in the importance of employees’ parents. Researchers infrequently address the role of parents in the work-family field. The aim of this thesis was to understand the influence of employees’ parents on work-family balance and its related outcomes in a Chinese society, Taiwan. A multi-method approach was employed consisting of three studies. First, the nature of the influence of employees’ parents in Taiwan was explored through interviews, followed by an online questionnaire survey with Taiwanese employees to examine the relationships between the influence of employees’ parents, work-family balance, organisational behaviour and wellbeing. Third, a secondary data analysis was used to provide triangulations for the findings of the questionnaire survey.